THE INFLUENCE OF AMERICAN DREAM TO THE CHARACTERIZATION OF WILLY LOMAN’S IN ARTHUR MILLER’S NOVEL - Muh Arif (Jurnal Ilmiah Administrasita', 2014)
This research aims at describing the influence of American Dream on Willy Loman’s characterization as a husband, father, and a salesman. The research applied a library research to collect information about the Death of a Salesman, American Dream and the author, Arthur Miller In doing the analysis, the writer used the structural method and sociological approach. The data were analyzed the characterization of Willy Loman by using structural approach, the writer continued her analysis to find out the influence of American Dream on Willy Loman’s characterizations by using sociological approach. The result of the research shows that WillyLoman’s characterizations are influenced by his ambition to pursue his American Dream. Willy Loman’s dream for being successful salesman and as a father makes him disappointed after he knows that he is fired from Howard’s Company and when he realizes that Biff in 34 years old does not has a proper job with a big salary. The realities make Willy Loman feels that he has failure in his life.